Critical analysis of an extensionist intervention (Research, Society and Development, 2022)
Technical assistance and rural extension (ATER) are fundamental services in the process of social and economic reproduction of rural populations, and can go beyond the transfer of new technologies, valuing knowledge from rural communities, expanding the participatory perspective and promoting rural development . Thus, the present work aims to carry out a critical analysis of Project A according to its intrinsic characteristics and extensionist approach. As a methodological strategy, a qualitative approach was used, which will be developed from a documentary analysis of collections provided by the entity. The appreciation of the character of Project A was carried out through content analysis, which provided the following categories of analysis: Social Inclusion, Capacity Building, Educational, Ecological and Environmental Process. In addition, the participatory extension approach was analyzed according to the indications of Haverroth (2012) and Valente (2005). The results obtained show that Project A promotes inclusion through the creation of a space for dialogue and learning of a professional activity for People with Disabilities (PwDs), as well as attention to ableism. The project had an adequate educational process for the students, which involved theory, practice and psychomotor development. Regarding the ecological and environmental aspect, the project was able to teach about recycling, sustainability and made it possible for them to become disseminators of sustainability. The analysis of the diffusionist approach showed that Project A, despite having a strong influence from the participatory approach, also has characteristics of the diffusionist and systemic approaches.